Composite tritium-resistant coating and preparation method thereof
By preparing FeAl/Al2O3 tritium-retardant coating on the surface of stainless steel and growing nano-multilayer films on its surface, the problem of defects when preparing tritium-retardant coating on the surface of large-size complex components is solved, and the tritium-retardant performance is achieved efficiently, meeting the PRF value requirements of CFETR under high temperature conditions.
Patent Information
- Application Number
- CN202411497984.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has defects in preparing FeAl/Al2O3 tritium-retardant coatings on the surface of large-sized complex components, which makes it difficult to improve tritium-retardant performance and cannot meet the requirement that the PRF value of tritium-retardant coatings under 500℃ gas phase conditions proposed by China Engineering Fusion Experimental Reactor (CFETR) is greater than 10,000.
FeAl/Al2O3 tritium-retardant coating was prepared on the stainless steel surface by aluminized, aluminized and in-situ oxidized, and nano-multilayer films with periodic thickness characteristics were grown on the surface of the FeAl/Al2O3 tritium-retardant coating through atomic layer deposition technology, including alternately deposited TiO2 and Al2O3 nanofilms to cover the defects in the coating and increase the number of interfaces.
By reducing the impact of defects on coating performance and capturing hydrogen isotopes through the interface, the tritium resistance performance of the composite tritium resistance coating is significantly improved, meeting the PRF value requirements of CFETR under high temperature conditions.
Smart Images

Figure CN119530907A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a composite tritium barrier coating and a preparation method thereof. Background Art
[0002] Tritium has a very small atomic radius, so it can easily penetrate through structural materials, causing problems such as hydrogen embrittlement of structural materials, energy waste, and radioactive safety. At present, preparing a tritium barrier coating of a certain thickness on the surface of structural materials can effectively solve the problem of tritium penetration. Tritium barrier coatings can be divided into oxide coatings, non-oxide coatings, and composite tritium barrier coatings. Among them, FeAl / Al2O3 tritium barrier coatings have the advantages of high tritium permeation reduction factor (PRF), excellent radiation resistance, and good corrosion resistance, so they are the preferred candidate coatings for experimental blankets.
[0003] The current methods for preparing FeAl / Al2O3 tritium barrier coatings mainly include physical vapor deposition, embedding, hot-dip aluminum and room temperature molten salt electrodeposition. Among them, room temperature molten salt electrodeposition has attracted widespread attention due to its advantages such as simple equipment and applicability to coating of complex-shaped surfaces. In the prior art, FeAl / Al2O3 tritium barrier coatings were successfully prepared on the surface of 321 stainless steel by the method of aluminum electrodeposition and aluminization combined with oxidation.
[0004] However, the FeAl / Al2O3 tritium barrier coating prepared on the surface of large-scale complex components by the current method has inevitable defects and other problems, which is still far from the requirement of the China Engineering Fusion Test Reactor (CFETR) that the PRF value of the tritium barrier coating should be greater than 10,000 under 500°C gas phase conditions. This is because defects will become a shortcut for hydrogen isotope penetration, and the "barrel effect" of defects will greatly affect the performance of the tritium barrier coating, making it difficult to significantly improve the performance of the tritium barrier coating. Therefore, to improve the tritium barrier performance of the tritium barrier coating, on the one hand, the coating itself should be made denser; on the other hand, the impact of defects on the coating performance should be alleviated as much as possible. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide a composite tritium barrier coating and a preparation method thereof. The composite tritium barrier coating reduces the influence of defects on the coating performance, utilizes the interface as a capture "trap" for hydrogen isotopes, and comprehensively improves the tritium barrier performance of the composite tritium barrier coating, and is suitable for the preparation of engineered tritium barrier coatings.
[0006] To achieve the above object, the present invention is implemented by adopting the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a composite tritium barrier coating, comprising:
[0008] Aluminum is plated on the surface of the pretreated stainless steel, and then aluminized to form a Fe-Al gradient layer on the surface of the stainless steel, wherein the Fe-Al gradient layer includes a Fe2Al5 layer located on the surface;
[0009] removing the Fe2Al5 layer in the Fe-Al gradient layer, and then performing in-situ oxidation on the surface of the Fe-Al gradient layer to form an Al2O3 layer to obtain a FeAl / Al2O3 tritium barrier coating;
[0010] A nano multilayer film with periodic thickness characteristics is deposited on the surface of the FeAl / Al2O3 tritium barrier coating to obtain a composite tritium barrier coating;
[0011] The nano multilayer film includes a first nanofilm and a second nanofilm deposited alternately, the first nanofilm includes a TiO2 nanofilm or a HfO2 nanofilm, and the second nanofilm includes an Al2O3 nanofilm or a ZrO2 nanofilm.
[0012] Further, the pretreatment includes: sanding the stainless steel, followed by ultrasonic cleaning;
[0013] And / or, the stainless steel comprises 316L stainless steel.
[0014] Furthermore, the aluminum plating on the pretreated stainless steel surface comprises:
[0015] The pretreated stainless steel is placed in an AlCl3-EMIC solution for electrochemical corrosion, the corrosion time is 7-13 minutes, the corrosion current is 0.05-0.08 A, and the corroded stainless steel is obtained;
[0016] The corroded stainless steel is used as the cathode, the Al wire with a purity of not less than 99.9% is used as the anode, and the AlCl3-EMIC solution is used as the electrolyte to carry out electrochemical aluminum deposition. The deposition time is 40-60 min and the deposition current is 0.1-0.15 A.
[0017] Furthermore, the aluminizing treatment includes: placing the stainless steel with aluminum plated on the surface in a tube furnace, and heat treating it in a vacuum environment at 700-750° C. for 8-10 h.
[0018] Furthermore, the in-situ oxidation on the surface of the Fe-Al gradient layer includes: placing the stainless steel with the Fe-Al gradient layer formed on the surface in a tube furnace, and in-situ oxidation for 8-12 hours in an air atmosphere at 700-750°C.
[0019] Furthermore, the deposition of a nano multilayer film having a periodic thickness characteristic on the surface of the FeAl / Al2O3 tritium barrier coating comprises:
[0020] The stainless steel with FeAl / Al2O3 tritium barrier coating is placed in the chamber of the atomic layer deposition equipment, the chamber is evacuated and the temperature is increased;
[0021] First, a layer of Al2O3 film is deposited on the surface of the FeAl / Al2O3 tritium barrier coating, and then a first nanofilm and a second nanofilm are alternately deposited according to a preset periodic thickness until the thickness of the nano multilayer film reaches a preset thickness.
[0022] Furthermore, the total thickness of each of the first nanofilm and the second nanofilm deposited is 3-15 nm; the thickness of the nano multilayer film is 100-200 nm.
[0023] Furthermore, a layer of Al2O3 film is first deposited on the surface of the FeAl / Al2O3 tritium barrier coating, and the thickness of the Al2O3 film is 3-5 nm.
[0024] Furthermore, a dry pump is used to evacuate the chamber of the atomic layer deposition equipment.
[0025] In a second aspect, the present invention provides a composite tritium barrier coating, which is prepared by the method for preparing the composite tritium barrier coating described in the first aspect.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The preparation method of the composite tritium barrier coating provided by the present invention prepares the FeAl / Al2O3 tritium barrier coating on the surface of stainless steel by a method of aluminum plating, aluminum diffusion and in-situ oxidation, and grows a nano multilayer film on the surface of the FeAl / Al2O3 tritium barrier coating by atomic layer deposition technology, wherein the nano multilayer film comprises a first nanofilm and a second nanofilm deposited alternately, the first nanofilm comprises a TiO2 nanofilm or a HfO2 nanofilm, the second nanofilm comprises an Al2O3 nanofilm or a ZrO2 nanofilm, and the materials such as Al2O3, TiO2 and HfO2 have good permeability to hydrogen isotopes. The nano multilayer film prepared by atomic layer deposition technology can cover the defects in the Al2O3 coating, reducing the influence of the defects on the coating performance; and by changing the periodic thickness of the nano multilayer film, the number of interfaces between the thin films of different materials in the nano multilayer film can be increased, and these interfaces can be used as "traps" for capturing hydrogen isotopes to inhibit the diffusion of hydrogen isotopes, thereby improving the tritium barrier performance of the composite tritium barrier coating; therefore, growing the nano multilayer film on the surface of the Al2O3 layer by atomic layer deposition technology can greatly improve the tritium barrier performance of the composite coating.
[0028] The method for preparing the composite tritium barrier coating provided by the present invention is suitable for preparing coatings on the surface of large and complex samples, and is therefore suitable for preparing engineered tritium barrier coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A schematic diagram of a process for preparing a composite tritium barrier coating provided in an embodiment of the present invention;
[0030] Figure 2 A cross-sectional scanning electron microscope image of a sample after electrodeposition aluminum plating and aluminizing provided by an embodiment of the present invention;
[0031] Figure 3 Scanning electron microscope images of the surface of different regions of the sample after the in-situ oxidation step provided by the embodiment of the present invention;
[0032] Figure 4 Surface scanning electron microscope images of Al2O3 / TiO2 nano-multilayer film samples with different period thicknesses deposited by atomic layer deposition provided by an embodiment of the present invention;
[0033] Figure 5 A cross-sectional transmission electron microscope image of a composite tritium barrier coating sample having a periodic thickness of 3 nm provided in an embodiment of the present invention;
[0034] Figure 6 A cross-sectional transmission electron microscope image of a defective region of a composite tritium barrier coating sample with a periodic thickness of 3 nm and a corresponding element distribution mapping image provided by an embodiment of the present invention;
[0035] Figure 7 Arrhenius plots of deuterium permeability and temperature for composite tritium barrier coating samples with different period thicknesses and 316L substrates provided in embodiments of the present invention.
[0036] In the figure: 1. 316L stainless steel sample; 2. Sample after aluminum plating; 3. Sample after aluminizing; 4. Sample after in-situ oxidation; 5. Sample after deposition of nano multilayer film. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for preparing a composite tritium barrier coating. Figure 1 As shown, the following steps are included:
[0040] Step 1), substrate pretreatment and AlCl3-EMIC electrolyte preparation:
[0041] 316L stainless steel discs were polished with 400#, 800#, 1200# and 2000# sandpapers in turn. Subsequently, the polished discs were ultrasonically cleaned with a mixed solution of ethanol and acetone. In a glove box, 1-ethyl-3-methylimidazole chloride (EMIC) and anhydrous AlCl3 with a mass ratio of 1:1.8 were weighed and placed in two beakers, and then AlCl3 was slowly poured into the beaker containing EMIC and stirred continuously with a glass rod. Subsequently, the ionic liquid was stirred with a constant temperature magnetic stirrer until all particles were dissolved to obtain an AlCl3-EMIC solution.
[0042] Step 2), preparation of FeAl / Al2O3 tritium barrier coating
[0043] ① Electrodeposition aluminum plating:
[0044] The cleaned 316L stainless steel disc was placed in a glove box. First, in order to remove the oxide layer on the stainless steel surface, the stainless steel disc was placed in an AlCl3-EMIC solution for electrochemical corrosion for 10 min, with a corrosion current of 0.07 A. Then, the stainless steel disc was used as the cathode, the high-purity Al wire as the anode, and the AlCl3-EMIC solution as the electrolyte for electrochemical aluminum deposition, with a deposition current of 0.1 A. After 45 min of deposition, the stainless steel disc was taken out and the residual liquid on the surface was wiped clean. The thickness of the Al layer on the stainless steel surface was about 16 μm.
[0045] ②Aluminizing:
[0046] Place the aluminum-plated stainless steel disc in the tube furnace and wait for the vacuum pump to pump to 1×10 -4 Pa and then subjected to heat treatment. The heat treatment temperature was 700 °C and the treatment time was 8 h, and a Fe-Al gradient layer was obtained, wherein the Fe-Al gradient layer included a Fe2Al5 layer located on the surface, and the sample was polished with a 2.5 μm suspension to polish and remove the Fe2Al5 layer on the surface.
[0047] ③In-situ oxidation:
[0048] The polished aluminized sample was placed in a tube furnace and in-situ oxidized at 700 °C for 10 h in air atmosphere. After oxidation, an Al2O3 layer of about 90 nm was successfully formed on the surface of the sample, thus obtaining the FeAl / Al2O3 tritium barrier coating.
[0049] Step 3), Deposition of Al2O3 / TiO2 nano-multilayer film
[0050] The in-situ oxidized sample was placed in the chamber of the atomic layer deposition equipment, the chamber was evacuated using a dry pump, and the sample was heated to 100 °C. Trimethylaluminum and ultrapure water are precursors for depositing Al2O3, while 4,2-methylaminotitanium and water are precursors for depositing TiO2. First, a 3 nm Al2O3 layer was deposited on the surface of the sample, and then an Al2O3 / TiO2 nano-multilayer film with a periodic thickness of 15 nm was deposited, specifically: TiO2 was deposited first, then Al2O3 was deposited, the sum of the thickness of the single-layer Al2O3 nano-film and the single-layer TiO2 nano-film was 15 nm, until the total thickness of the nano-multilayer film was about 150 nm.
[0051] Example 2
[0052] This embodiment provides a method for preparing a composite tritium barrier coating, which is different from Embodiment 1 in that:
[0053] Step 3), Deposition of Al2O3 / TiO2 nano-multilayer film
[0054] The in-situ oxidized sample was placed in the chamber of the atomic layer deposition equipment, the chamber was evacuated using a dry pump, and the sample was heated to 100 °C. Trimethylaluminum and ultrapure water were the precursors for depositing Al2O3, while 4,2-methylaminotitanium and water were the precursors for depositing TiO2. First, a 3 nm Al2O3 layer was deposited on the sample surface, and then an Al2O3 / TiO2 nano-multilayer film with a periodic thickness of 7.5 nm was deposited until the total thickness of the nano-multilayer film was about 150 nm.
[0055] Example 3
[0056] This embodiment provides a method for preparing a composite tritium barrier coating, which is different from Embodiment 1 in that:
[0057] Step 3), Deposition of Al2O3 / TiO2 nano-multilayer film
[0058] The in-situ oxidized sample was placed in the chamber of the atomic layer deposition equipment, the chamber was evacuated using a dry pump, and the sample was heated to 100 °C. Trimethylaluminum and ultrapure water were the precursors for depositing Al2O3, while 4,2-methylaminotitanium and water were the precursors for depositing TiO2. First, a 3 nm Al2O3 layer was deposited on the sample surface, and then an Al2O3 / TiO2 nano-multilayer film with a periodic thickness of 3 nm was deposited until the total thickness of the nano-multilayer film was about 150 nm.
[0059] Example 4
[0060] This embodiment provides a composite tritium barrier coating, and the composite tritium barrier coating is prepared by the following method:
[0061] Aluminum is plated on the surface of the pretreated stainless steel, and then aluminized to form a Fe-Al gradient layer on the surface of the stainless steel, wherein the Fe-Al gradient layer includes a Fe2Al5 layer located on the surface;
[0062] removing the Fe2Al5 layer in the Fe-Al gradient layer, and then performing in-situ oxidation on the surface of the Fe-Al gradient layer to form an Al2O3 layer to obtain a FeAl / Al2O3 tritium barrier coating;
[0063] A nano multilayer film with periodic thickness characteristics is deposited on the surface of the FeAl / Al2O3 tritium barrier coating to obtain a composite tritium barrier coating;
[0064] Wherein, the nano multilayer film is Al2O3 and HfO2 deposited alternately.
[0065] Example 5
[0066] This embodiment provides a composite tritium barrier coating, and the composite tritium barrier coating is prepared by the following method:
[0067] Aluminum is plated on the surface of the pretreated stainless steel, and then aluminized to form a Fe-Al gradient layer on the surface of the stainless steel, wherein the Fe-Al gradient layer includes a Fe2Al5 layer located on the surface;
[0068] removing the Fe2Al5 layer in the Fe-Al gradient layer, and then performing in-situ oxidation on the surface of the Fe-Al gradient layer to form an Al2O3 layer to obtain a FeAl / Al2O3 tritium barrier coating;
[0069] A nano multilayer film with periodic thickness characteristics is deposited on the surface of the FeAl / Al2O3 tritium barrier coating to obtain a composite tritium barrier coating;
[0070] Wherein, the nano multilayer film is ZrO2 and HfO2 deposited alternately.
[0071] Figure 2 The cross-sectional scanning electron microscope images of the aluminum-plated and aluminum-diffused samples prepared in Example 1, (a) is a cross-sectional scanning electron microscope image of the sample after electrodeposition aluminum plating, and (b) is a cross-sectional scanning electron microscope image of the sample after aluminum diffusion. After electrodeposition aluminum plating, an Al layer with a thickness of about 16μm was successfully prepared on the surface of 316L stainless steel. The Al layer is uniform and dense, and is tightly bonded to the substrate. After aluminization, Al and the substrate elements diffused with each other to form a three-layer Fe-Al transition layer, which is Fe2Al5, FeAl2 and Fe3Al layers from top to bottom.
[0072] Figure 3The surface scanning electron microscope images of different regions of the sample prepared in Example 1 after in-situ oxidation, (a) is the surface scanning electron microscope image of the dense region of the sample, (b) is the surface scanning electron microscope image of the defective region of the sample. Figure 3 (a) It can be seen that the Al2O3 layer is flat and dense, but Figure 3 (b) It can be seen that defects such as holes are formed in some areas due to the unevenness of the substrate elements.
[0073] Figure 4 The surface scanning electron microscope images of the samples after the Al2O3 / TiO2 nano multilayer film was deposited on the surface, wherein Figure (a1-a2) is the surface scanning electron microscope images of different regions of the composite tritium barrier coating sample with a periodic thickness of 15nm prepared in Example 1, Figure (b1-b2) is the surface scanning electron microscope images of different regions of the composite tritium barrier coating sample with a periodic thickness of 7.5nm prepared in Example 2, and Figure (c1-c2) is the surface scanning electron microscope images of different regions of the composite tritium barrier coating sample with a periodic thickness of 3nm prepared in Example 3. As can be seen from the figure, after the Al2O3 layer is deposited with Al2O3 / TiO2 nano multilayer films of different periodic thicknesses, the sample surface becomes smoother, and the defects such as holes existing in some areas are covered by the deposited multilayer film.
[0074] Figure 5 (a) is a cross-sectional transmission electron microscope image of a nano-multilayer film sample deposited with a periodic thickness of 3 nm prepared in Example 3. Figure 5 (b) is a cross-sectional transmission electron microscopy image of the nano-multilayer film at high magnification. As can be seen from the figure, an Al2O3 layer of about 90 nm was successfully formed after in-situ oxidation at 700 °C for 10 h. The Al2O3 layer is flat and dense, and is tightly bonded to the Fe-Al layer. The interface of the Al2O3 / TiO2 nano-multilayer film is clear, and no obvious defects are observed at high magnification.
[0075] Figure 6The cross-sectional transmission electron microscope image of the defective area of the Al2O3 / TiO2 nano-multilayer film sample deposited with a periodic thickness of 3 nm prepared in Example 3 and the corresponding element distribution mapping diagram. Among them, Figures (a) and (b) are the bright field image and HAADF image of the defective area, respectively, and Figure (ch) is the element distribution mapping diagram corresponding to the defective area. It can be seen from the figure that the aluminum oxide layer formed in the defective area is very chaotic and cannot hinder the penetration of hydrogen isotopes. At the same time, it can be seen from the Fe and O element distribution mapping diagram that the defective area is also accompanied by the oxidation of the Fe element, which further affects the tritium barrier performance of the coating. The multilayer film deposited by ALD successfully covers the surface of the defect and blocks the channel for tritium diffusion and penetration, thereby avoiding the "barrel effect" and greatly reducing the impact of defects on the tritium barrier performance of the coating.
[0076] The permeability of the Al2O3 / TiO2 nano-multilayer composite tritium barrier coating samples with different period thicknesses prepared in Example 1, Example 2 and Example 3 and the 316L substrate was tested by the self-built instrument. The instrument is divided into a high pressure side (HPV) and a low pressure side (LPV). The two chambers are separated by the sample and are connected to a set of vacuum pumps. The ultimate vacuum can reach 1×10 -6 Pa. The sample is heated to 450-550 °C in a tube furnace. During the test, 40 kPa of D2 is introduced to the HPV side through a leak valve, and the quadrupole mass spectrometer on the LPV side continuously measures the D partial pressure. By comparing the D partial pressure of the coating sample with that of the 316L substrate, the PRF value of the sample can be calculated. Figure 7 Arrhenius curves of permeability and temperature of composite tritium barrier coating samples with different periodic thicknesses prepared in Example 1, Example 2 and Example 3 and 316L substrate. The PRF values of the FeAl / Al2O3 coating prepared by electrochemical aluminum plating, aluminum diffusion and in-situ oxidation at 450°C and 500°C are 6950 and 1100 respectively. Since there are a certain number of defects in the original Al2O3 coating, D2 will pass through the defective area more easily at high temperatures, so the performance of the coating at high temperatures is significantly deteriorated. After Al2O3 / TiO2 nano-multilayer films with different periodic thicknesses are deposited on the surface, the performance of the composite tritium barrier coating has been greatly improved.
[0077] As a control experiment, the deuterium barrier performance of Al2O3 / TiO2 nano-multilayer film samples with a period thickness of 15 nm grown directly on a 316L substrate was also tested. At 500 °C, the PRF values of the Al2O3 / TiO2 nano-multilayer film (15 nm) and the composite tritium barrier coating with Al2O3 / TiO2 nano-multilayer film (15 nm) covered on the surface of the FeAl / Al2O3 coating were 7600 and 46000, respectively. This shows that the interface alone is not enough to make the composite tritium barrier coating have a PRF value as high as 46000. Therefore, another reason for the performance improvement is that the multilayer film covers the defects in the original FeAl / Al2O3 coating, thereby reducing the impact of the defects on the coating performance. And the composite tritium barrier coating shows higher performance with the increase in the number of interfaces. This is because hydrogen isotopes have lower formation energy near the interface, that is, they are more stable at the interface. Therefore, the interface acts as a "trap" for the capture of hydrogen isotopes, thereby inhibiting the diffusion of hydrogen isotopes. The coating sample with the smallest periodic thickness (3 nm) and the largest number of interfaces has a PRF value of up to 5×10 5 , which far exceeds the requirement proposed by CFETR that the PRF value of the tritium barrier coating should be greater than 10,000 under 500°C gas phase conditions.
[0078] Since materials such as Al2O3, TiO2 and HfO2 have good inhibitory effects on the penetration of hydrogen isotopes, the selection of multilayer film materials is relatively diversified. The nano multilayer film prepared by atomic layer deposition technology can cover the defects in the Al2O3 coating, reducing the impact of defects on the coating performance. In addition, the interface can be used as a capture "trap" for hydrogen isotopes to inhibit the diffusion of hydrogen isotopes. By changing the periodic thickness of the nano multilayer film, the number of interfaces can be increased, thereby improving the tritium barrier performance of the composite tritium barrier coating. Therefore, the growth of Al2O3 / TiO2, Al2O3 / HfO2 or ZrO2 / HfO2 nano multilayer films on the surface of the Al2O3 layer by atomic layer deposition technology can greatly improve the tritium barrier performance of the composite coating. And considering that both electrochemical deposition and ALD can be applied to the preparation of coatings on the surface of large and complex samples, the present invention has great potential in the preparation of future engineered tritium barrier coatings.
[0079] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.
Claims
1. A method for preparing a composite tritium barrier coating, characterized in that: include: Aluminum is plated on the surface of the pretreated stainless steel, and then aluminized to form a Fe-Al gradient layer on the surface of the stainless steel, wherein the Fe-Al gradient layer includes a Fe2Al5 layer located on the surface; removing the Fe2Al5 layer in the Fe-Al gradient layer, and then performing in-situ oxidation on the surface of the Fe-Al gradient layer to form an Al2O3 layer to obtain a FeAl / Al2O3 tritium barrier coating; A nano multilayer film with periodic thickness characteristics is deposited on the surface of the FeAl / Al2O3 tritium barrier coating to obtain a composite tritium barrier coating; The nano multilayer film includes a first nanofilm and a second nanofilm deposited alternately, the first nanofilm includes a TiO2 nanofilm or a HfO2 nanofilm, and the second nanofilm includes an Al2O3 nanofilm or a ZrO2 nanofilm.
2. The method for preparing the composite tritium barrier coating according to claim 1, characterized in that: The pretreatment includes: sanding the stainless steel, followed by ultrasonic cleaning; And / or, the stainless steel comprises 316L stainless steel.
3. The method for preparing the composite tritium barrier coating according to claim 1, characterized in that: The aluminum plating on the pretreated stainless steel surface comprises: The pretreated stainless steel is placed in an AlCl3-EMIC solution for electrochemical corrosion, the corrosion time is 7-13 min, the corrosion current is 0.05-0.08 A, and the corroded stainless steel is obtained; The corroded stainless steel is used as the cathode, the Al wire with a purity of not less than 99.9% is used as the anode, and the AlCl3-EMIC solution is used as the electrolyte to carry out electrochemical aluminum deposition. The deposition time is 40-60 min and the deposition current is 0.1-0.15 A.
4. The method for preparing the composite tritium barrier coating according to claim 1, characterized in that: The aluminizing treatment comprises: placing the surface-aluminized stainless steel in a tube furnace and heat treating it in a vacuum environment at 700-750° C. for 8-10 h.
5. The method for preparing the composite tritium barrier coating according to claim 1, characterized in that: The in-situ oxidation on the surface of the Fe-Al gradient layer comprises: placing the stainless steel with the Fe-Al gradient layer formed on the surface in a tube furnace, and in-situ oxidation for 8-12 hours in an air atmosphere at 700-750°C.
6. The method for preparing the composite tritium barrier coating according to claim 1, characterized in that: The method of depositing a nano multilayer film having a periodic thickness characteristic on the surface of the FeAl / Al2O3 tritium barrier coating comprises: The stainless steel with FeAl / Al2O3 tritium barrier coating is placed in the chamber of the atomic layer deposition equipment, the chamber is evacuated and the temperature is increased; First, a layer of Al2O3 film is deposited on the surface of the FeAl / Al2O3 tritium barrier coating, and then a first nanofilm and a second nanofilm are alternately deposited according to a preset periodic thickness until the thickness of the nano multilayer film reaches a preset thickness.
7. The method for preparing the composite tritium barrier coating according to claim 6, characterized in that: The total thickness of each of the first nanofilm and the second nanofilm deposited is 3-15 nm; the thickness of the nano multilayer film is 100-200 nm.
8. The method for preparing the composite tritium barrier coating according to claim 6, characterized in that: The method first deposits a layer of Al2O3 film on the surface of the FeAl / Al2O3 tritium barrier coating, wherein the thickness of the Al2O3 film is 3-5 nm.
9. The method for preparing the composite tritium barrier coating according to claim 6, characterized in that: A dry pump is used to evacuate the chamber of the atomic layer deposition equipment.
10. A composite tritium barrier coating, characterized in that: The method is prepared by any one of claims 1 to 9.